Impact of Urbanization on Air Quality in Kenya - Odhiambo, Jack (International Journal of Environmental Sciences, 2021)
Purpose: To aim of the study was to analyze the impact of urbanization on air quality in Kenya. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Urbanization in Kenya has significantly increased PM2.5 levels and CO2 emissions, particularly in densely populated cities like Nairobi, driven by rapid population growth, traffic congestion, and industrial activities. Studies show that industrial emissions and reliance on fossil fuels exacerbate air pollution, posing serious public health risks such as respiratory and cardiovascular diseases. Recommendations highlight the need for stricter emission standards, expanded public transport, green spaces, and sustainable urban planning to mitigate the negative effects of urbanization on air quality. Unique Contribution to Theory, Practice and Policy: Urban ecological theory, sustainable development theory & environmental kuznets curve (EKC) may be used to anchor future studies on the impact of urbanization on air quality in Kenya. To mitigate the impact of urbanization on air quality, it is essential to incorporate green infrastructure in urban planning. Policymakers should focus on strengthening air quality regulations and their enforcement to reduce pollution levels in major African cities.